Review of Fvidence Analysis and Reporting Phases in Digital Forensics Process - Varol, Asaf; Sonmez, Yesim Ulgen (Ieee, 2017)
This paper reviews digital forensic phases and problems in evidence analysis phase and smart methods in this area. Among these phases, studies on the evidence analysis phase are examined. In the analysis of electronic evidences, use of smart methods and their development will contribute to information technology law and improvement of digital forensic devices. Effective evidence analysis both provides easiness for digital forensic experts and helps jurists tor accurate decisions. In this paper, digital forensic process and smart methods used in evidence analysis are examined. This literature survey discussed which new methods can be added to this process.
2017 International Conference on Computer Science and Engineering (UBMK) -- OCT 05-08, 2017 -- Antalya, TURKEY
Keywords: Digital forensics phases; evidence analysis phase; smart methods